New pathogenic PTPN2 variant leading to childhood interstitial lung disease. - Rowbotham,NJ; Jeanpierre,M; Bush,A; Jagani,S; Jones,G; Warrier,K; Parlato,M; Rieux-Laucat,F; Bhatt,JM (Thorax, 2026)
Protein tyrosine phosphatase non-receptor type 2 (PTPN2) is a tyrosine phosphatase involved in T cell receptor signal transduction and cytokine response. Loss of function variants have previously been linked with immune mediated diseases such as inflammatory bowel disorders, rheumatoid arthritis and type 1 diabetes. We present a case of childhood interstitial lung disease with a newly identified pathogenic (PTPN2) gene variant in a boy aged 4 years.